Transmembrane Shuttling of Photosynthetically Produced Electrons to Propel Extracellular Biocatalytic Redox Reactions in a Modular Fashion. Issue 40 (26th August 2022) - Jurkaš, Valentina; Weissensteiner, Florian; De Santis, Piera; Vrabl, Stephan; Sorgenfrei, Frieda A.; Bierbaumer, Sarah; Kara, Selin; Kourist, Robert; Wangikar, Pramod P.; Winkler, Christoph K.; Kroutil, Wolfgang
Abstract: Many biocatalytic redox reactions depend on the cofactor NAD(P)H, which may be provided by dedicated recycling systems. Exploiting light and water for NADPH‐regeneration as it is performed, e.g. by cyanobacteria, is conceptually very appealing due to its high atom economy. However, the current use of cyanobacteria is limited, e.g. by challenging and time‐consuming heterologous enzyme expression in cyanobacteria as well as limitations of substrate or product transport through the cell wall. Here we establish a transmembrane electron shuttling system propelled by the cyanobacterial photosynthesis to drive extracellular NAD(P)H‐dependent redox reactions. The modular photo‐electron shuttling (MPS) overcomes the need for cloning and problems associated with enzyme‐ or substrate‐toxicity and substrate uptake. The MPS was demonstrated on four classes of enzymes with 19 enzymes and various types of substrates, reaching conversions of up to 99 % and giving products with >99 % optical purity. Abstract : Water is utilized as benign electron‐donor in photosynthesis, e.g. by cyanobacteria. Herein, a novel approach to shuttle them through the cyanobacterium's cell‐membrane and to utilize them for extracellular NAD(P)H‐dependent redox reactions is presented. The concept was demonstrated for 19 different reductive and oxidative enzymes from 4 different classes.